Community awareness on the implementation of early warning system at Tenaga Nasional Berhad Sultan Abu Bakar hydroelectric scheme, Lembah Bertam, Cameron Highland - Mohd. Hussain, Mohd. Ramzi; Zen, Ismawi; Sabri Muda, Rahsidi; Thiruchelvam, Sivadass; Tukiman, Izawati; Ahmad Shazili, Aishah Naqiah (Planning Malaysia, 2018)
This article presents the community awareness on the implementation of Early Warning System (EWS) in a well-planned Integrated Community-Based Disaster Management (ICBDM) that covers all Tenaga Nasional Berhad’s (TNB) hydroelectric schemes. In Cameron Highland, Lembah Bertam and further downstream villages were reported to have the highest occurrence of floods especially during monsoon season, which makes the area vulnerable. This study incorporates and synergizes three major stakeholders; the community; local authority; and TNB; gearing towards minimizing loss of life and property damages in the event of a dam related disaster. The aim of this article is to assess the level of awareness and perceptions of the directly affected communities towards the implementation of EWS. Their heightened awareness would help to reduce their vulnerability in the event of future disaster. This study opted for a quantitative approach, which included a questionnaire survey. The findings revealed that the demographic characteristics influenced community awareness regarding the implementation of EWS. Most of the respondents accepted the EWS positively and understood the importance of EWS. Thus, the community members have the right to know and understand the hazard they should be expecting so they can plan for themselves and make informed choices to reduce their vulnerability.